Performance Evaluation of Performance Evaluation of Emergency Medical Service Systems with Multiple Ambulance Types and Patient Types - Arumugaraj Nadar, Raviarun; Jha, J.K.; Thakkar, Jitesh J. (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
Emergency medical services (EMS) are an important part of the modern healthcare system that tries to provide timely medical care and transportation to patients to reduce morbidity and mortality. Performance evaluation of such EMS systems to determine measures such as mean service rates, dispatch probabilities, busy probabilities, and on-scene times is necessary to design effective and efficient systems. In this paper, we consider an urban EMS system that employs three types of emergency vehicles, including advanced life support (ALS), basic life support (BLS) and first responder vehicle (FRV). We consider two types of patients: type A requires ALS to be dispatched, while type B patients are expected to be served by BLS ambulances. We also consider co-located servers so ambulances of different types can be co-located at the same station. The presence of different types of servers (ambulances) and the patients with different dispatch policies, along with co-located servers, makes it applicable to a more realistic system. We first discuss a modification of the hypercube queueing model for the proposed system and then present an approximate approach for application in large EMS systems. These approaches are compared against a simulation-based model by computing server utilization, service times and on-scene time of ambulances.